Low-adsorption wear-resistant coating and preparation method thereof

By using a design combining a nickel-based amorphous coating with a textured layer in the surface coating, the existing coating has solved the problems of low hardness and poor wear resistance, and achieved high hardness, high bonding force, low adsorption and excellent tribological properties, which significantly improved the wear resistance and corrosion resistance of the coating.

CN119640191APending Publication Date: 2025-03-18SCI RES TRAINING CENT FOR CHINESE ASTRONAUTS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411687470.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the prior art, the surface coating has low hardness, poor wear resistance, poor corrosion resistance, high adsorption and low bonding force between the substrate and the coating, resulting in premature failure of the coating in harsh environments, increasing maintenance costs and affecting the safety and reliability of the equipment.

Method used

A low adsorption wear-resistant coating is adopted, including the first texture layer and the second texture layer, and the nickel-based amorphous coating is between the two texture layers, and is prepared by a laser device for texture processing and plasma spraying technology to improve the hardness and bonding force of the coating, and reduce adsorption and friction coefficient.

Benefits of technology

It achieves high hardness, high bonding force, low adsorption and excellent tribological properties, significantly improves the wear and corrosion resistance of the coating, extends the service life of the equipment and reduces maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640191A_ABST
    Figure CN119640191A_ABST
Patent Text Reader

Abstract

The invention relates to a low-adsorption wear-resistant coating, which comprises a first texture layer, a second texture layer and a third texture layer, the nickel-based amorphous coating is attached to the first texture layer; the second texture layer is radiated on the nickel-based amorphous coating; a first texture pattern is arranged in the first texture layer, and the shape of the first texture pattern is at least one of a circle, a triangle, a rhombus and a grid-shaped pit array; a second texture pattern is arranged in the second texture layer and is in the shape of at least one of a round pit array, a triangular pit array, a diamond pit array and an arrowhead pit array. The first texture layer and the second texture layer are respectively textured on the surface of the substrate and the surface of the coating, so that the coating is high in hardness, high in wear resistance, corrosion-resistant and low in adsorbability, and the binding force between the substrate and the coating is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of friction and wear, and specifically relates to a low-adsorption wear-resistant coating and a preparation method thereof. Background Art

[0002] In industrial applications, many mechanical equipment and components need to operate in harsh working environments, such as high temperature, high pressure, corrosive media, etc. These conditions place higher requirements on the surface properties of materials.

[0003] Chinese patent CN107387553B mentions that the outer spherical surface of the bearing is textured, and the surface texture is processed by self-lubricating material friction pre-filling technology to form a self-lubricating material friction pre-filling type surface texture structure; the inner spherical surface of the outer ring of the bearing is bonded with a layer of fabric self-lubricating material liner, and the above design is a solid lubricating film. Although the friction coefficient can be reduced to a certain extent by coating the solid lubricating film after the coating surface is textured, in some occasions with high hardness requirements, the solid lubricating film is difficult to meet the requirements of parts for high hardness and high load-bearing capacity under harsh working conditions. Most of the current composite processing technologies are aimed at the possible fracture of the coating during the friction and wear process and the generation of a large number of abrasive particles. The texture can store abrasive particles, but it does not take into account that if the coating surface has high adsorption, the abrasive particles will adhere to the coating surface and are not easy to enter the pits. Severe abrasive wear will cause the coating to fail.

[0004] Although traditional coating technology can provide a certain degree of protection, it often has problems such as insufficient wear resistance, poor corrosion resistance and strong adsorption, which can lead to premature failure of the coating, increase maintenance costs, and even affect the safety and reliability of the equipment. In order to solve the above problems, researchers have been exploring new coating materials and preparation technologies. These studies include the development of new coating materials, such as ceramic coatings, metal ceramic coatings and amorphous coatings, as well as the use of advanced coating technologies such as physical vapor deposition (PVD), chemical vapor deposition (CVD) and plasma spraying technology. These new coatings and preparation technologies have improved the performance of the coating to a certain extent, but they still face challenges in practical applications, such as insufficient bonding between the coating and the substrate, difficulty in ensuring the uniformity and density of the coating, and limited adaptability of the coating. In addition, the surface structure of the coating is also an important factor affecting its performance. The microstructure of the coating surface can affect its friction coefficient, wear rate and corrosion resistance.

[0005] Therefore, how to improve the hardness, wear resistance, corrosion resistance, adsorption of the surface coating and enhance the bonding strength between the substrate and the coating is an urgent problem to be solved in the field of friction and wear technology. Summary of the invention

[0006] The purpose of the present invention is to solve the problems existing in the prior art of low hardness, poor wear resistance, poor corrosion resistance, high adsorption and low bonding strength between the substrate and the coating of the surface coating.

[0007] The purpose of the present invention is to adopt the following technical solutions to achieve:

[0008] A low adsorption wear-resistant coating is provided, comprising:

[0009] A first texture layer radiates on the substrate surface;

[0010] A nickel-based amorphous coating, attached to the first texture layer;

[0011] a second texture layer, irradiated onto the nickel-based amorphous coating;

[0012] The first texture layer is provided with a first texture pattern, and the shape of the first texture pattern is at least one of a circular, triangular, diamond and grid-shaped pit array;

[0013] The second texture layer is provided with a second texture pattern, and the shape of the second texture pattern is at least one of a circular, triangular, diamond and arrow-shaped pit array.

[0014] Furthermore, the substrate is at least one of aluminum alloy, nickel-based alloy, stainless steel and silicon wafer.

[0015] Furthermore, the low-adsorption wear-resistant coating has a thickness of 200 to 400 μm.

[0016] Furthermore, the thickness of the first texture layer is 30-90 μm.

[0017] Furthermore, the width of the pits in the first texture pattern is 50-200 μm.

[0018] Furthermore, the area ratio of the pits in the first texture pattern is 5% to 30%.

[0019] Furthermore, the thickness of the second texture layer is 10-70 μm.

[0020] Furthermore, the width of the pits in the second texture pattern is 50-200 μm.

[0021] Furthermore, the area ratio of the pits in the second texture pattern is 4% to 19.6%.

[0022] The method for preparing the low-adsorption wear-resistant coating as described in any one of the above items comprises the following steps:

[0023] Grinding, polishing, and cleaning the surface of the substrate;

[0024] Using a laser device to perform texturing on the surface of the substrate to obtain the first texture layer;

[0025] Producing a nickel-based amorphous coating on the surface of the first texture layer by plasma spraying;

[0026] Using a laser device to perform texturing treatment on the surface of the nickel-based amorphous coating to obtain the second texture layer;

[0027] The second texture layer is cleaned twice to obtain the low-adsorption wear-resistant coating.

[0028] Furthermore, the cleaning agent is selected from at least one of acetone, ethanol and water.

[0029] Furthermore, the sandpaper used for grinding and polishing is 200-2500 mesh.

[0030] Furthermore, the secondary cleaning includes: placing the low-adsorption wear-resistant coating in anhydrous ethanol for cleaning, and drying it with argon gas after cleaning.

[0031] Furthermore, the secondary cleaning time is 20 to 40 minutes.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] A low adsorption wear-resistant coating comprising:

[0034] A first texture layer radiates on the substrate surface;

[0035] A nickel-based amorphous coating, attached to the first texture layer;

[0036] a second texture layer, irradiated onto the nickel-based amorphous coating;

[0037] The first texture layer is provided with a first texture pattern, and the shape of the first texture pattern is at least one of a circular, triangular, diamond and grid-shaped pit array;

[0038] The second texture layer is provided with a second texture pattern, and the shape of the second texture pattern is at least one of a circular, triangular, diamond and arrow-shaped pit array.

[0039] In view of the defects of the prior art, the present invention aims to overcome the increasingly stringent requirements for high hardness, high bonding strength, and friction reduction and wear resistance of surface coatings with the rapid development of industrial engineering in recent years. The plasma spray coating preparation technology precisely controlled by an automated manipulator and mature laser surface micromachining technology are used to complete the parameter design of the texturing of the coating surface and the interface texturing combined with the substrate. From the two perspectives of the coating surface and the substrate surface, a textured coating preparation process with high hardness, high bonding strength, low adsorption and excellent tribological properties is provided to improve the service life of engine bearings in dusty or harsh environments. The low surface energy coating can reduce the adsorption of solid particles because the interaction force between the solid particles and the coating surface is weak and they are not easy to adhere.

[0040] By using plasma spraying technology, the coating has a higher hardness, and laser processing texture at the interface between the coating and the substrate can improve the bonding strength between the coating and the substrate and reduce the risk of coating peeling;

[0041] Laser processing of the coating surface into micro-nano structures can reduce the surface friction coefficient and improve wear resistance; and the textured coating has low surface energy and low adsorption.

[0042] By forming a second texture layer on the surface of the nickel-based amorphous coating, the stress concentration on the coating surface can be further dispersed and alleviated, and the local wear during the wear process can be reduced, thereby improving the overall wear resistance.

[0043] While achieving wear resistance and drag reduction to improve the mechanical properties of the metal surface, it also has multifunctional properties such as chip storage, wear reduction, oil storage, and lubrication. The textured coating surface has low adsorption. As the wear intensifies during the friction process, abrasive particles fall off the surface of the friction pair material, or hard particles such as sand or certain metal fragments slide or roll over the surface of the part under pressure, generating a large number of abrasive particles. The abrasive particles are not easy to adhere to the coating surface, and the abrasive particles are more likely to slide and roll into the pits, making it difficult to cause secondary wear to the coating surface.

[0044] The present invention not only improves the wear resistance of the surface of parts, but also the surface of the textured coating has low adsorption. As the wear intensifies during the friction process, abrasive particles peel off from the surface of the friction pair material, or hard particles such as sand or certain metal fragments slide or roll over the surface of the parts under pressure, generating a large number of abrasive particles. The abrasive particles are not easy to adhere to the coating surface, and the abrasive particles are more likely to slide and roll into the pits, which makes it difficult to cause secondary wear to the coating surface.

[0045] The surface texturing of the substrate improves the coating's resistance to crack propagation, and the surface texturing of the substrate increases the coating's adhesion area and mechanical meshing force. The textured substrate with a strengthening layer provides a better bearing surface for coating adhesion, and the good degree of coordinated deformation between the textured substrate and the layer enhances the deformation resistance of the coating system.

[0046] Substrate texturing improves the crack resistance of the coating and enhances the adhesion of the coating. The textured surface pattern provides a bearing surface for the coating and enhances the deformation resistance.

[0047] The technical content of the present invention includes preparation methods and performance testing, and proposes a low-adsorption and high-wear-resistant coating preparation process method and application. The textured nickel-based amorphous coating provided by the present invention has mechanical properties such as high hardness, corrosion resistance, and high bonding strength. The key point is that it has friction reduction, wear resistance and low absorption, which is conducive to promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 It is a three-dimensional topography image of the laser textured substrate surface of the present invention;

[0049] Figure 2 Schematic diagram of the circle, triangle and diamond of the laser texture on the coating surface of the present invention;

[0050] Figure 3 This is a comparison chart of the coating microhardness test results of Test Example 1 of the present invention;

[0051] Figure 4 Schematic diagram of friction and wear experiment of Test Example 2 of the present invention;

[0052] Figure 5 This is a comparison chart of the friction coefficients obtained from the friction and wear experiment of Test Example 2 of the present invention;

[0053] Figure 6 This is a scanning electron microscope comparison diagram of the corrosion experiment of Test Example 3 of the present invention;

[0054] Figure 7 Schematic diagram of the contact angle test results of Test Example 4 of the present invention. DETAILED DESCRIPTION

[0055] The technical solution provided by the present invention is described in detail below by way of specific embodiments:

[0056] like Figure 1 As shown, a low adsorption wear-resistant coating comprises:

[0057] A first texture layer radiates on the substrate surface;

[0058] The first texture layer on the substrate surface can increase the contact area between the coating and the substrate, thereby improving the adhesion of the coating; the texture pattern in the first texture layer can change the microstructure of the coating surface, thereby affecting the surface properties of the coating, such as friction coefficient, surface roughness, etc.; by designing a suitable texture pattern shape in the first texture layer, the surface properties of the coating can be optimized to adapt to specific application environments and requirements. The texture pattern can serve as the starting point of microcracks in the coating, which helps to control the crack propagation path, thereby improving the fatigue resistance of the coating.

[0059] A nickel-based amorphous coating attached to the first textured layer;

[0060] A second textured layer, radiated on the nickel-based amorphous coating;

[0061] By forming a second texture layer on the surface of the nickel-based amorphous coating, the stress concentration on the coating surface can be further dispersed and alleviated, and the local wear during the wear process can be reduced, thereby improving the overall wear resistance.

[0062] The first texture layer is provided with a first texture pattern, and the shape of the first texture pattern is at least one of a circular, triangular, diamond-shaped and grid-shaped pit array;

[0063] The second texture layer is provided with a second texture pattern, and the shape of the second texture pattern is at least one of a circular, triangular, diamond and arrow-shaped pit array.

[0064] The substrate is at least one of aluminum alloy, nickel-based alloy, stainless steel and silicon wafer.

[0065] A low adsorption wear-resistant coating with a thickness of 200 to 400 μm. The above design can enhance corrosion resistance, improve fatigue wear life, optimize tribological properties, increase hardness and strength, achieve economic and material efficiency, adjust performance according to intended use, improve impact resistance, and reduce maintenance costs while improving wear resistance.

[0066] The thickness of the first texture layer is 30-90 μm, the width of the pits in the first texture pattern is 50-200 μm, and the area ratio of the pits in the first texture pattern is 5%-30%. The above design can bring significant benefits in improving the bonding strength of the coating, optimizing tribological properties, improving lubrication properties, enhancing fatigue resistance, improving thermal conductivity, strong adaptability, improving impact resistance, and reducing maintenance costs.

[0067] The thickness of the second texture layer is 10-70 μm, the width of the pits in the second texture pattern is 50-200 μm, and the area rate of the pits in the second texture pattern is 4%-19.6%. The texture pattern can improve the tribological performance through microfluidic dynamic pressure, "secondary lubrication" effect, abrasive "storage" effect and contact area reduction effect, which help reduce friction, reduce wear, and provide a more stable lubrication effect under different working conditions. Under lubrication conditions, the texture can produce fluid dynamic pressure effect or play a "secondary oil supply" role, thereby reducing the friction of the contact surface of the friction pair and improving the wear resistance of the material. The appropriate depth and width of the texture pattern can serve as a reservoir for lubricants, which helps to keep the lubricant continuously lubricated to the surface during movement. The texture pattern can capture and store wear debris to avoid secondary damage to the coating during friction, thereby improving the wear resistance of the coating. By adjusting the depth and width of the texture pattern, the microstructure of the surface can be adjusted, thereby affecting the surface properties of the coating, such as friction coefficient, surface roughness, etc.

[0068] The method for preparing the above-mentioned low-adsorption wear-resistant coating comprises the following steps:

[0069] Clean the substrate with a detergent to effectively remove oil and impurities on the surface and ensure the bonding strength between the coating and the substrate;

[0070] The surface of the substrate is polished with sandpaper and then ultrasonically cleaned. Through sandpaper polishing and ultrasonic cleaning, the impurities and oxide layer remaining on the surface are further removed to improve the adhesion of the coating.

[0071] Using laser equipment to texture the surface of the substrate to obtain a first texture layer;

[0072] A plasma spray gun is used to spray the atomized Ni60 powder onto the substrate to form a nickel-based amorphous coating on the surface of the substrate;

[0073] Laser equipment is used to texture the surface of the nickel-based amorphous coating to obtain a second texture layer and a low-adsorption wear-resistant coating. The surface of the nickel-based amorphous coating is subjected to secondary texturing to further optimize the surface properties of the coating, reduce the friction coefficient, and improve the fatigue resistance.

[0074] The washing agent is selected from at least one of acetone, ethanol and water.

[0075] The specifications of sandpaper are 200-2500 mesh.

[0076] The low-absorption wear-resistant coating was placed in anhydrous ethanol for a second cleaning, blown dry with argon gas after cleaning, wrapped with dust-free cloth and placed in a plastic bag for later use.

[0077] The second cleaning time is 20 to 40 minutes.

[0078] The present invention utilizes plasma spraying technology, and the coating has a relatively high hardness. In addition, laser processing of texture at the interface between the coating and the substrate can improve the bonding strength between the coating and the substrate and reduce the risk of coating peeling. Laser processing of the surface of the coating into a micro-nano structure can reduce the surface friction coefficient and improve wear resistance. The textured coating has low surface energy and low adsorption.

[0079] While achieving wear resistance and drag reduction to improve the mechanical properties of the metal surface, it also has multifunctional properties such as chip storage, friction reduction, oil storage, and lubrication. The textured coating surface has low adsorption. As the wear intensifies during the friction process, abrasive particles peel off from the surface of the friction pair material, or hard particles such as sand or certain metal fragments slide or roll over the surface of the part under pressure, generating a large number of abrasive particles. The abrasive particles are not easy to adhere to the coating surface, and the abrasive particles are more likely to slide and roll into the pits, making it difficult to cause secondary wear to the coating surface. The texturing of the substrate surface improves the coating's resistance to crack propagation, and the substrate surface texture increases the coating's adhesion area and mechanical meshing force. The textured substrate with a strengthening layer provides a better bearing surface for coating adhesion, and the good degree of coordinated deformation between the textured substrate and the layer enhances the deformation resistance of the coating system.

[0080] Example 1

[0081] A low adsorption wear-resistant coating comprising:

[0082] A first texture layer radiates on the substrate surface;

[0083] A nickel-based amorphous coating attached to the first textured layer;

[0084] A second textured layer, radiated on the nickel-based amorphous coating;

[0085] The first texture layer is provided with a first texture pattern, and the shape of the first texture pattern is at least one of a circular, triangular, diamond-shaped and grid-shaped pit array;

[0086] The second texture layer is provided with a second texture pattern, and the shape of the second texture pattern is at least one of a circular, triangular, diamond and arrow-shaped pit array.

[0087] The method for preparing the above-mentioned low-adsorption wear-resistant coating comprises the following steps:

[0088] Aluminum alloy is selected as the substrate, and it is cleaned with a washing agent to remove surface dirt and impurities. The specific steps of washing are: the substrate 1 is washed with acetone, ethanol and water in sequence for 25 minutes; and then dried in a drying oven at 50°C for 75 minutes.

[0089] The surface of the substrate was polished with sandpaper of 200-2500 mesh and then ultrasonically cleaned. Polishing can avoid the influence of substrate surface roughness and debris on the laser processing process, remove the residual grinding paste and oil on the surface of the sample after polishing, obtain a clean surface, and avoid inconsistent refractive index of the laser between samples, which affects the subsequent judgment of texture size.

[0090] The surface of the substrate is textured using laser equipment to obtain the first texture layer. The specific steps are: Use the laser equipment to prepare the surface micro-texture for the YLP-MP20 laser marking machine. The laser is mainly composed of IPGMOPA fiber laser, main control system, software operating system, and German ScanLab galvanometer system. The laser outputs a laser beam with a wavelength of 1064nm during operation. After the beam is expanded by a beam expander and reflected by the galvanometer system, the laser beam moves on a two-dimensional plane under the action of the control system. The laser beam is focused by a focusing lens, and finally a fine high-energy spot is formed on the surface of the sample, which instantly vaporizes the processed surface; it is radiated point by point on the surface of the sample according to the pre-set pattern, and finally a texture morphology with a certain depth and width is formed.

[0091] The geometric parameters of the first texture pattern of laser texturing on the substrate surface include pattern design, diameter, area ratio and depth, where the pattern design is a circular pit array; since the depth of the texture pattern is an important parameter affecting the bonding strength of the spray coating, the depth of the texture pattern shows a certain regularity with the change of laser processing parameters. Increasing the laser processing power, reducing the laser processing speed and increasing the number of laser impacts during the laser processing process will increase the depth of the texture pattern. By adjusting the parameters of the laser processing process, the first texture layer is obtained by laser texturing on the substrate surface. The thickness of the first texture layer is 30μm, the diameter of the pits of the first texture pattern is 50μm, and the pit area ratio is a circular array of 5%. Specific processing parameters: laser power is 13.5W, scanning speed is 800mm / s, number of processing is 1 time, and the three-dimensional morphology of the substrate texture is as follows: Figure 1 shown.

[0092] The nickel-based amorphous coating is prepared by plasma spraying equipment. The specific steps are as follows: the atomized Ni60 powder is sprayed on the substrate using a plasma spray gun to form a nickel-based amorphous coating on the substrate surface. The specific operation steps are as follows: the plasma spray gun used is an F4 spray gun, and the substrate is heated to 120°C before spraying. The power supply selected for plasma spraying is a DC power supply, and its dynamic and external characteristics meet the requirements of the plasma arc generated by the spray gun. The spraying parameters include argon flow rate, spraying current and spraying distance. The specific parameters used after optimization are argon flow rate: 110L / min, spraying current: 450A, spraying voltage: 135V, spraying distance: 120mm, powder feeding rate: 3.5g / min, and powder feeding gas flow rate: 9L / min. The Ni60 powder after gas atomization treatment is sprayed using an F4 spray gun, and its diameter is 15-45μm. The chemical composition of the Ni60 powder is shown in Table 1 below.

[0093] Table 1 Ni60 amorphous powder composition (mass fraction, %)

[0094]

[0095] like Figure 2 As shown, after a nickel-based amorphous coating with a thickness of about 300 μm is sprayed on the surface of the substrate by plasma spraying, the surface of the nickel-based amorphous coating is laser textured. The geometric parameters of the second texture pattern include pattern design, diameter, area ratio and depth, wherein the pattern design is a circular pit array, the thickness of the second texture layer is 10 μm, the diameter of the pits of the second texture pattern is 50 μm, and the pit area ratio is 4% of the circular array.

[0096] After laser texturing of the coating surface, it needs to be cleaned for the second time. During cleaning, the sample is placed in anhydrous ethanol medium, and the working time of the cleaning machine is set to 30 minutes. After cleaning, it is blown dry with argon gas, wrapped with dust-free cloth and stored in a plastic bag for later use. Through the above-mentioned parameter laser texturing parameter design, the weak links of the coating are strengthened to improve the interface bonding strength, the overall stability and improve the structural integrity of the coating, and the coating surface is textured. Through the coupling effect of the substrate surface and the coating surface texture pattern, the coating performance is ultimately greatly improved.

[0097] Embodiment 2-6

[0098] The low adsorption wear-resistant coating provided in Example 2-6 has raw material contents as shown in Table 2 below:

[0099] Table 2 Different raw material ratios

[0100]

[0101] The preparation method of the low adsorption wear-resistant coating provided in Examples 2-6 is the same as that in Example 1, except that the preparation conditions are different, as shown in Table 3:

[0102] Table 3 Summary of preparation conditions of the examples

[0103]

[0104] Comparative Example 1

[0105] A low adsorption wear-resistant coating comprising:

[0106] Nickel-based amorphous coating adheres to the surface of the substrate.

[0107] The method for preparing the above-mentioned low-adsorption wear-resistant coating comprises the following steps:

[0108] Aluminum alloy is selected as the substrate, and it is cleaned with a washing agent to remove surface dirt and impurities. The specific steps of washing are: the substrate 1 is washed with acetone, ethanol and water in sequence for 25 minutes; and then dried in a drying oven at 50°C for 75 minutes.

[0109] The surface of the substrate was polished with sandpaper of 200-2500 mesh and then ultrasonically cleaned. Polishing can avoid the influence of substrate surface roughness and debris on the laser processing process, remove the residual grinding paste and oil on the surface of the sample after polishing, obtain a clean surface, and avoid inconsistent refractive index of the laser between samples, which affects the subsequent judgment of texture size.

[0110] The nickel-based amorphous coating is prepared by plasma spraying equipment. The specific steps are as follows: the atomized Ni60 powder is sprayed on the substrate using a plasma spray gun to form a nickel-based amorphous coating on the substrate surface. The specific operation steps are as follows: the plasma spray gun used is an F4 spray gun, and the substrate is heated to 120°C before spraying. The power supply selected for plasma spraying is a DC power supply, and its dynamic and external characteristics meet the requirements of the plasma arc generated by the spray gun. The spraying parameters include argon flow rate, spraying current and spraying distance. The specific parameters used after optimization are argon flow rate: 110L / min, spraying current: 450A, spraying voltage: 135V, spraying distance: 120mm, powder feeding rate: 3.5g / min, and powder feeding gas flow rate: 9L / min. The Ni60 powder after gas atomization treatment is sprayed using an F4 spray gun, and its diameter is 15-45μm. The chemical composition of the Ni60 powder is shown in Table 1 below.

[0111] Table 1 Ni60 amorphous powder composition (mass fraction, %)

[0112]

[0113] Test Example 1

[0114] like Figure 3 As shown, microhardness test: When the coating has a higher hardness, its wear resistance and fatigue resistance are better to a certain extent. To a certain extent, the higher the hardness of the coating, the better the wear resistance and fatigue resistance. Therefore, the present invention uses HVS-1000A digital display microhardness tester to test the cross-sectional hardness of the coating samples of Example 1 and Comparative Example 1 at a distance of 50 μm.

[0115] In the test results, the hardness of Example 1 is significantly higher than that of Comparative Example 1, with a hardness value of up to 775 HV. 0.2 This result shows that the hardness of the coating is significantly improved by the preparation method of the present invention, and this improvement is inseparable from the structural design of the first texture layer and the second texture layer. The nickel-based amorphous coating usually contains high-hardness carbide and boride particles, which are evenly distributed in the coating, enhancing the overall hardness of the coating.

[0116] In practical applications, high-hardness coatings can effectively resist wear and extend service life, especially in high-load and high-impact working environments. The increase in hardness can significantly reduce the risk of coating peeling and fatigue failure. In addition, the increase in hardness also helps to improve the coating's scratch resistance, making it more advantageous when the friction pair is in contact.

[0117] In summary, the results of the microhardness test verify the advantages of the low-adsorption wear-resistant coating of the present invention in terms of hardness, which provides strong technical support for its application in aerospace, engineering machinery and other fields; by improving the hardness of the coating, it can effectively cope with harsh working conditions and meet the high requirements of modern industry for material performance.

[0118] Test Example 2

[0119] like Figure 4 As shown, friction and wear experiment: the experimental instrument adopts a high-speed reciprocating friction and wear testing machine, and the test parameters are as follows: the coating surface of Example 1 and Comparative Example 1 is subjected to oil friction test, and the test parameters are as follows: the wear scar length is 1.5mm, the test frequency is 10Hz, the load is 80N, the friction time is 30min, the test method is reciprocating friction, and the friction ball is made of Si3N4 material with a diameter of 6.36mm.

[0120] The friction and wear test is intended to evaluate the tribological properties of the coating under actual working conditions. By comparing the coatings of Example 1 and Comparative Example 1, the wear resistance of the coating can be intuitively understood.

[0121] like Figure 5As shown, the friction coefficient of Example 1 is significantly lower than that of Comparative Example 1. This result shows that the coating preparation method of the present invention exhibits better wear resistance and lower friction loss during the friction process. This performance improvement is related to the texturing treatment of the coating surface in the present invention. The textured surface can effectively reduce the friction contact area and reduce the generation of friction heat, thereby reducing the friction coefficient.

[0122] In addition, low friction coefficient not only helps to reduce wear, but also improves energy efficiency and reduces energy consumption. In industrial applications, reducing friction coefficient can significantly extend the service life of equipment and reduce maintenance costs. Therefore, the results of friction and wear experiments provide strong support for the feasibility of the low adsorption wear-resistant coating of the present invention in practical applications.

[0123] In summary, the results of the friction and wear experiments show that the low-adsorption wear-resistant coating of the present invention has significant advantages in tribological properties, which enables it to effectively reduce wear and improve the reliability and economy of equipment under high load and high frequency working conditions.

[0124] Test Example 3

[0125] Corrosion test: Example 1 and Comparative Example 1 were subjected to 72h weak alkali and weak acid salt spray tests respectively.

[0126] In industrial applications, the corrosion resistance of the coating is one of the key factors that determine its service life and performance. In the experiment, the coatings of Example 1 and Example 2 were subjected to 72 hours of weak alkali and weak acid salt spray tests, respectively. This accelerated corrosion test can simulate the chemical erosion that the coating may encounter in the actual environment.

[0127] like Figure 6 As shown, after a long period of salt spray test, the coating of Example 1 has no obvious rust on the surface, showing excellent corrosion resistance, indicating that the coating has strong chemical stability, can effectively resist the erosion of corrosive media, and prolong the service life of the coating. This result is particularly important for the application of coatings in corrosive environments such as aerospace, chemical industry, and marine engineering.

[0128] In contrast, the coating of Comparative Example 1 exhibits obvious rust under the same corrosion conditions, and this comparison further highlights the superior performance of the coating of the present invention.

[0129] This improvement in corrosion resistance is related to the textured design of the coating, because the textured surface can reduce the porosity of the coating and reduce the chance of corrosive media penetrating into the interface between the coating and the substrate.

[0130] In summary, the results of Test Example 3 show that the low-adsorption wear-resistant coating of the present invention has significant advantages in corrosion resistance, which is crucial for the application of the coating in harsh environments. By improving the corrosion resistance of the coating, the maintenance cost can be effectively reduced, the service life of the equipment can be extended, and the market competitiveness of the coating can be enhanced.

[0131] Test Example 4

[0132] Contact angle test: The German Dataphysics-OCA20 contact angle tester was used to measure the water contact angle on the sample surface. By dropping 2μl of distilled water onto the surface of the untextured sample and the textured sample, a high-resolution video camera was used to monitor the contact angle in real time. The contact angle was measured using the tangent method. In order to ensure the accuracy of the measurement results, each sample was tested 5 times and the average value was calculated, which is the contact angle results measured for the samples of Example 5 and Comparative Example 1. Control group A is the contact angle of water on the surface of the sample of Comparative Example 1, and its contact angle is 80.1°. Control group B is the laser-processed surface of the sample of Example 5, and its contact angle is 110.5°. The wettability of the coating surface changes from hydrophilic to hydrophobic, and has low adsorption.

[0133] Contact angle test is an important experiment to evaluate the wettability of coating surface, which can reflect the hydrophilicity or hydrophobicity of coating. Figure 7 As shown, the contact angle of Example 5 is 110.5°, which is significantly higher than 80.1° of Comparative Example 1. This result shows that the coating surface of Example 5 changes from hydrophilic to hydrophobic, with lower surface energy and lower adsorption. Hydrophobic coatings have multiple advantages in practical applications. First, they can effectively prevent the adhesion of moisture and pollutants, reducing the frequency of surface cleaning and maintenance; second, hydrophobic surfaces can reduce the lubricating effect of liquids during friction, thereby reducing the friction coefficient and improving wear resistance.

[0134] In addition, the hydrophobic coating exhibits better stability in high temperature or humid environments and can effectively prevent corrosion and oxidation, which makes the low-adsorption wear-resistant coating of the present invention more widely and reliably used in the fields of aerospace, engineering machinery, etc.

[0135] In summary, the results of the contact angle test show that the low-adsorption wear-resistant coating of the present invention has significant advantages in surface wettability, which provides a good basis for its application in various harsh environments and further improves the comprehensive performance and application value of the coating.

[0136] Test Example 5

[0137] A surface scratch tester was used to apply a positive load to the surface coatings applied on Example 1 and Comparative Example 1, respectively. The substrate and the test diamond indenter slid relatively slowly, gradually increasing the load until the coating peeled off, and recording the load intensity of the coating peeling off. Whether the coating peeled off can be determined by the fluctuation of the pattern of the acoustic sensor. The greater the load intensity when the coating peeled off, the higher the bonding strength between the coating and the substrate.

[0138] The bonding strength of the coating is evaluated by a surface scratch tester. This test simulates the mechanical peeling that the coating may encounter during actual use. The bonding strength between the coating and the substrate is measured by gradually increasing the load until the coating peels off. During the test, whether the coating peels off can be determined by the fluctuation of the acoustic sensor graph. The greater the load intensity, the higher the bonding strength between the coating and the substrate.

[0139] Example 1 shows a high load strength, indicating that the bond between the coating and the substrate is very strong. This high strength bond is due to the texturing of the coating surface, which increases the contact area between the coating and the substrate, thereby improving the mechanical meshing force. In addition, the textured surface also promotes chemical bonding between the coating and the substrate, further enhancing the bond strength.

[0140] In summary, the results of Test Example 5 verify the advantages of the low adsorption wear-resistant coating of the present invention in terms of bonding strength, which provides strong technical support for its application in high-load and high-impact environments. By improving the bonding strength between the coating and the substrate, the reliability and durability of the coating can be effectively improved, meeting the needs of modern industry for high-performance coatings.

[0141] The present invention utilizes the advantages of combining plasma spraying and laser processing. While achieving wear resistance and drag reduction and improving the mechanical properties of the metal surface, the surface texture can store lubricants, thereby providing a continuous lubricating medium between the contact surfaces of the friction pairs. In addition, the textured coating has low adsorption, which means that the interaction between the coating surface and the abrasive particles is weak, which helps to reduce the adhesion of the abrasive particles on the surface. Therefore, during the sliding process, the pits can capture the debris generated during the wear process, thereby reducing abrasive wear.

[0142] The present invention also has the following advantages:

[0143] 1. The textured coating surface has low surface energy and low adsorption capacity, and is contaminated with fewer solid particles in dusty environments. Dust particles are not easy to accumulate on the coating surface, thereby reducing potential damage caused by dust accumulation.

[0144] 2. According to the particle size distribution of solid particles in conventional dusty environments, a variable-size pit structure is designed to effectively store solid particles.

[0145] 3. The low adsorption of textured coating will reduce the adhesion of abrasive particles. During the friction and wear process, the abrasive particles can easily slide into the texture pits, reducing the risk of secondary wear.

[0146] 4. The textured nickel-based coating has a low friction coefficient. Through the convex structure design (the result of the combined effects of laser-induced material evaporation, melting, solidification and other processes), the low friction design of the coating is achieved without adding secondary processes such as sulfurization.

[0147] 5. Achieve high wear resistance design. The ability of the non-textured substrate surface to store lubricating oil is poor. As the friction process proceeds, the lubrication state between the friction pairs quickly changes to dry friction, which makes the wear marks on the surface of the friction ball larger and causes wear debris adhesion on its surface. That is, laser texturing can not only slow down the wear of the coating surface, but also slow down the wear of the friction ball surface.

[0148] 6. The surface texture of the substrate increases the adhesion area and mechanical meshing force of the coating. The textured substrate with a strengthening layer provides a better bearing surface for coating adhesion and enhances the deformation resistance of the coating system.

[0149] The above are merely embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are included in the scope of the claims of the present invention to be approved.

Claims

1. A low adsorption wear-resistant coating, characterized in that: include: A first texture layer radiates on the substrate surface; A nickel-based amorphous coating, attached to the first texture layer; a second texture layer, irradiated onto the nickel-based amorphous coating; The first texture layer is provided with a first texture pattern, and the shape of the first texture pattern is at least one of a circular, triangular, diamond and grid-shaped pit array; The second texture layer is provided with a second texture pattern, and the shape of the second texture pattern is at least one of a circular, triangular, diamond and arrow-shaped pit array.

2. A low adsorption wear-resistant coating as claimed in claim 1, characterized in that: The substrate is at least one of aluminum alloy, nickel-based alloy, stainless steel and silicon wafer.

3. A low adsorption wear-resistant coating as claimed in claim 1, characterized in that: Its thickness is 200 to 400 μm.

4. A low adsorption wear-resistant coating as claimed in claim 1, characterized in that: The thickness of the first texture layer is 30-90 μm.

5. A low adsorption wear-resistant coating as claimed in claim 4, characterized in that: The width of the pits in the first texture pattern is 50-200 μm.

6. A low adsorption wear-resistant coating as claimed in claim 4, characterized in that: The area ratio of the pits in the first texture pattern is 5% to 30%.

7. A low adsorption wear-resistant coating as claimed in claim 1, characterized in that: The second texture layer has a thickness of 10 to 70 μm.

8. A low adsorption wear-resistant coating as claimed in claim 7, characterized in that: The width of the pits in the second texture pattern is 50-200 μm.

9. A low adsorption wear-resistant coating as claimed in claim 7, characterized in that: The area ratio of the pits in the second texture pattern is 4% to 19.6%.

10. The method for preparing a low-adsorption wear-resistant coating according to any one of claims 1 to 9, characterized in that: The following steps are involved: Grinding, polishing, and cleaning the surface of the substrate; Using a laser device to perform texturing on the surface of the substrate to obtain the first texture layer; Producing a nickel-based amorphous coating on the surface of the first texture layer by plasma spraying; Using a laser device to perform texturing treatment on the surface of the nickel-based amorphous coating to obtain the second texture layer; The second texture layer is cleaned twice to obtain the low-adsorption wear-resistant coating.

11. The method for preparing a low-adsorption wear-resistant coating according to claim 10, characterized in that: The cleaning agent is selected from at least one of acetone, ethanol and water.

12. The method for preparing a low-adsorption wear-resistant coating according to claim 10, characterized in that: The sandpaper used for the grinding and polishing is 200-2500 mesh.

13. A method for preparing a low adsorption wear-resistant coating as claimed in claim 10, characterized in that: The secondary cleaning comprises: placing the low-absorption wear-resistant coating into anhydrous ethanol for cleaning, and drying with argon gas after cleaning.

14. A method for preparing a low adsorption wear-resistant coating as claimed in claim 10, characterized in that: The secondary cleaning time is 20 to 40 minutes.

Citation Information

Patent Citations

  • Fabric-type surface textured friction pre-filled self-lubricating spherical bearing

    CN107387553B